Management Control System and Firm Performance: A Strategic Approach - Badollahi, Ismail; Nurhidayah; Upe, Ambo; Inam, Aneeq (Universitas Pendidikan Ganesha, 2024)
This research aims to examine the relationship between management control systems and firm performance through firm capability. The research used a survey method in processing industrial companies with a population of 137. The number of samples analyzed was 63 samples. The analytical tool used to test the hypothesis is Partial Least Square (PLS) with the help of smart PLS software version 4.0. The research results succeeded in proving a direct relationship between the management control system affecting firm capability, the management control system on firm performance, and firm capability on firm performance. Apart from that, the results of this research also prove that firm capability can mediate the relationship between the management control system and firm performance. This indicates that the company’s success in achieving optimal performance and achieving competitive advantage lies in the strategy of implementing the management control system and firm capability. Therefore, the company continues to improve its management control system and capability so that firm performance can improve and achieve competitive advantage.